STRATEGI PENDIDIKAN AGAMA ISLAM DI LAPAS ANAK KUTOARJO - Maisyanah Maisyanah (Jurnal Pendidikan Agama Islam, 2014)
There are four strategies that can be applied to achieve goals of Islamic education, which is the traditional strategy, clarification, exemplary, and transinternal. The results of field research shows that teachers in choosing a strategy is monotone. That is because PAI teachers not meet the academic qualifications and professional qualifications, limited facilities and infrastructure, in addition to the factors of learners in their own prisons are indeed special. Special because they are different from children who live in a normal environment. The purpose of Islamic education is to develop the physical and non-physical potential learners, so that they are able to carry out what they understand of learning to be applied in their daily lives. Therefore, the effectiveness of the strategy has not been fully successful monotony in relation to the learning process. Outside of learning, the learner has demonstrated good character or good behavior in the prisons. The author sees, supporting factors other than the strategy adopted in learning to foster learner’s personality is LAPAS environment that fully supports the development of potential learners with he designed programs tailored to the interests and talents of students through CLC institutions Tunas Mekar while this the building is still a part of the prisons.